Commoning care: Feminist degrowth visions for a socio-ecological transformation - Dengler, Corinna; Lang, Miriam (Feminist Economics, 2022)
This paper addresses the question of how to organize care in degrowth societies that call for social and ecological sustainability, as well as gender and environmental justice, without prioritizing one over the other. By building on degrowth scholarship, feminist economics, the commons, and decolonial feminisms, we rebut the strategy of shifting yet more unpaid care work to the monetized economy, thereby reinforcing the separation structure in economics. A feminist degrowth imaginary implies destabilizing prevalent dichotomies and overcoming the (inherent hierarchization in the) boundary between the monetized economy and the invisibilized economy of socio-ecological provisioning. The paper proposes an incremental, emancipatory decommodification and a commonization of care in a sphere beyond the public/private divide, namely the sphere of communitarian and transformative caring commons, as they persist at the margins of capitalism and are (re-)created by social movements around the world.HIGHLIGHTS Degrowth aims at creating human flourishing within planetary boundaries.As feminist degrowth scholarship, this study discusses degrowth visions for care work.It problematizes the shifting of yet more unpaid care work to the monetized economy.Instead, it proposes collective (re)organization in the sphere of the commons.Caring commons are no automatism for a gender-just redistribution of care work.
Keywords: approches et analyses; care; discipline; décroissance; environnement; féminisme décolonial; projet charge mentale; sciences de la gestion; thématiques; travail; travail du care; économie

Forms of Care: Chimamanda Ngozi Adichie’s Americanah (2014), Agency, and Decolonial Feminism - McCann, Fiona (Études littéraires africaines, 2021)
Cet article explore la politique féministe telle qu’elle est représentée dans le roman Americanah de Chimamanda Ngozi Adichie, ainsi que la manière dont ce féminisme s’entremêle avec des formes de care. Je cerne les contours de l’engagement affiché de l’autrice pour le féminisme intersectionnel, tout en pointant quelques angles morts. Après avoir situé l’oeuvre d’Adichie dans le contexte des féminismes postcolonial, populaire et décolonial, j’étudie l’importance des cheveux et la question plus générale de l’agentivité. Dans la dernière partie, je démontre que la poétique du care développée dans le roman n’adhère pas totalement au féminisme décolonial en raison de l’invisibilité relative des structures néo-coloniales à l’oeuvre au Nigeria pendant la période contemporaine.
Keywords: afro-féminisme; agentivité; approches et analyses; arts; care; discipline; féminisme décolonial; féminismes noirs; littérature; militance; politique; ressource en ligne; thématiques; études littéraires